Emotion Differentiation and Youth Mental Health: Current Understanding and Open Questions - Nook, Erik C. (Frontiers in Psychology, 2021)
A growing body of research identifies emotion differentiation—the ability to specifically identify one’s emotions—as a key skill for well-being. High emotion differentiation is associated with healthier and more effective regulation of one’s emotions, and low emotion differentiation has been documented in several forms of psychopathology. However, the lion’s share of this research has focused on adult samples, even though approximately 50% of mental disorders onset before age 18. This review curates what we know about the development of emotion differentiation and its implications for youth mental health. I first review published studies investigating how emotion differentiation develops across childhood and adolescence, and studies testing relations between emotion differentiation and mental health in youth samples. Emerging evidence suggests that emotion differentiation actually falls across childhood and adolescence, a counterintuitive pattern that merits further investigation. Similarly, several studies find relations between emotion differentiation and youth mental health, but some instability in results emerged. I then identify open questions that currently limit our understanding of emotion differentiation, including (i) lack of clarity as to the valid measurement of emotion differentiation, (ii) potential third variables that could explain relations between emotion differentiation and mental-health (e.g., mean negative affect, IQ, personality, and circularity with outcomes), and (iii) lack of clear mechanistic models regarding the development of emotion differentiation and how it facilitates well-being. I conclude with a discussion of future directions that can address open questions and work towards interventions that treat (or even prevent) psychopathology.